2002
DOI: 10.4102/jsava.v73i3.570
|View full text |Cite
|
Sign up to set email alerts
|

The effect of storage conditions on samples for the evaluation of copper status in blesbok (Damaliscus pygargus phillipsi)

Abstract: Investigaltions to determine the effect of sample storage on the concentration of copper in liver tissue and on the activity of erythrocyte superoxide dismutase were undertaken in preparation for a study of blesbok (<em>Damaliscus pygargus phillipsi</em>) that were suspected to be suffering from copper deficiency. Two liver samples were collected from each of 20 culled blesbok in a manner that simulated the collection of biopsies from the live animal. These samples were stored either in 10 % formal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…For the other elements, there were no detectable changes. In our study, substantial amounts of Mg and Mn were leached to the formalin ( [6] found that 4 1/2 months of formalin storage significantly reduced the Cu concentration in liver samples from blesbok, a South African antelope species. In addition, Hendrickx et al [7] reported that 14 days of formaldehyde storage substantially reduced (up to 40%) the Cu concentrations in three species of woodlice.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…For the other elements, there were no detectable changes. In our study, substantial amounts of Mg and Mn were leached to the formalin ( [6] found that 4 1/2 months of formalin storage significantly reduced the Cu concentration in liver samples from blesbok, a South African antelope species. In addition, Hendrickx et al [7] reported that 14 days of formaldehyde storage substantially reduced (up to 40%) the Cu concentrations in three species of woodlice.…”
Section: Resultsmentioning
confidence: 87%
“…However, Bush et al [2] reported that formalin storage resulted in decreased Mn and Mg and increased Al tissue levels, and Meldrum [4] reported decreases in Co and Al concentrations. Others have reported decreased Cu levels in liver tissue from an antelope species [6] and in woodlice [7] as an effect of storage in formalin.…”
Section: Introductionmentioning
confidence: 96%
“…The single nilgai (Puls 1994) and blesbok (Penrith et al 1996;Quan et al 2002) Cu levels were considerably lower than those recorded in the literature, but the liver Cu level in the addra gazelle was almost identical to that recorded in other captive gazelles (Wieckowski et al 2008). However, the liver Cu level in the 3-day-old Mhorr gazelle was much higher than that recorded in Thomson's gazelle.…”
Section: Coppermentioning
confidence: 64%
“…In other countries, the mineral status of zoo animals has been evaluated in black and white ruffed lemur (Varecia variegata) (Crawford et al 2009), black rhinoceros (Diceros bicornis) (Clauss et al 2007;Dierenfeld et al 2005), mule and white-tailed deer (Odocoileus hemionus, Odocoileus virginianus) (Zimmerman et al 2008) and pronghorn (Antilocapra americana) (Miller et al 2001). The mineral status of free-ranging wildlife has been measured in African buffalo (Syncerus caffer) (Webb et al 2001), black wildebeest (Connochaetes gnou) (Penrith et al 1996), blesbok (Damaliscus pygargus phillipsi) (Penrith et al 1996;Quan 2005;Quan, Mülders & Meltzer 2002), Kafue lechwe (Kobus leche kafuensis) (Syakalima et al 2000), springbok (Antidorcas marsupialis) (Hoon 2003) and Thompson's gazelle (Eudorcas thomsonii) (Wieckowski, Abraham & Wernery 2008). Evidence suggests that free-ranging species instinctively select forages that will balance some of their mineral requirements (McNaughton 1990).…”
Section: Introductionmentioning
confidence: 99%
“…Formalin, which is commonly used to preserve marine mammal tissues for histopathological examination and museum collections, has the potential to alter trace element concentrations; however, relatively few controlled experiments have been performed to determine the effects of formalin fixation on trace element concentrations in animal tissues, and the results have been variable. Some studies have found that formalin fixation does not alter tissue trace element concentrations, whereas other studies have found that formalin fixation significantly alters tissue trace element concentrations, either by increasing or decreasing concentrations, suggesting issues of contamination and leaching, respectively (Gibbs et al 1974; Theron et al 1974; Sullivan et al 1993; Koizumi et al 1994; Bush et al 1995; Renaud et al 1995; Meldrum 2001; Quan et al 2002; Sato et al 2006; Bischoff et al 2008; Gellein et al 2008; Hill et al 2010; Poulopoulos 2013). If formalin fixation does not impact tissue trace element concentrations or if it has consistent and predictable effects such that trace element concentrations in unpreserved tissues can be predicted from trace element concentrations in formalin‐fixed tissues, then such tissues may be useful not only for histopathological examination but also for toxicology studies (Renaud et al 1995; Sato et al 2006; Poulopoulos 2013; Campbell and Drevnick 2015).…”
Section: Introductionmentioning
confidence: 99%